PHYSICAL PROPERTIES AND ANTIOXIDANT ACTIVITY OF ESSENCE SHEET MASK WITH CONVENTIONAL AND HYDROPONIC RED SPINACH LEAF EXTRACT - Romadhiyana Kisno Saputri; Aprillia Dwi Ardianti; Ria Indah Kusuma Pitaloka; Musfirotun Ni'am; Nur Farlina; Siti Nur Afifta (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) UNSIQ, 2023)
Red spinach is a plant that known as natural antioxidants that contain anthocyanins, flavonoids, betalains, polyphenols and carotenoids and can be developed into sheet mask essence. The antioxidant activity of red spinach affected by the cultivation method. This study aims to determine the physical properties and antioxidant activity of conventional and hydroponic essences with red spinach leaf extract. The making of essence sheet mask starts from making red spinach leaf extract by maceration method using 96% ethanol as solvent for 3x24 hours, then the extract is added to the formulation. Physic evaluations were organoleptic tests including assessing shape, aroma and color by panelists, homogeneity that their data analyzed by descriptively, pH and viscosity analyzed by t-test. Test of antioxidant activity of spinach leaf extract using the DPPH method that analyzed by t-test. Conventional and hydroponic red spinach leaf extracts have a thick green color, thick form and a characteristic spinach odor, while essence sheet masks have a light green color, viscous liquid form and a distinctive fragrance, a safe pH value for facial skin, which is around 5.18 ± 0. 29 to 5.64±0.12, homogeneous and viscosity values ranged from 162.92±21.95 to 187.58±17.54 cps. Based on the results of t-test the pH and viscosity values of all formulations were not significantly different. The antioxidant activity of conventional and hydroponic red spinach leaf extract was in the strong category and not significant difference based on the t-test. The essence sheet mask has good physical properties and the IC50 value of conventional red spinach leaf extract is 52.53 and hydroponic red spinach leaf extract is 73.93.